Exchange Rate Management and Crisis Susceptibility : A Reassessment - Ghosh, Atish (IMF Working Papers; Working Paper ;, 2014)
This paper revisits the bipolar prescription for exchange rate regime choice and asks two questions: are the poles of hard pegs and pure floats still safer than the middle? And where to draw the line between safe floats and risky intermediate regimes? Our findings, based on a sample of 50 EMEs over 1980-2011, show that macroeconomic and financial vulnerabilities are significantly greater under less flexible intermediate regimes-including hard pegs-as compared to floats. While not especially susceptible to banking or currency crises, hard pegs are significantly more prone to growth collapses, suggesting that the security of the hard end of the prescription is largely illusory. Intermediate regimes as a class are the most susceptible to crises, but "managed floats"-a subclass within such regimes-behave much more like pure floats, with significantly lower risks and fewer crises. "Managed floating," however, is a nebulous concept; a characterization of more crisis prone regimes suggests no simple dividing line between safe floats and risky intermediate regimes.